2014
DOI: 10.1158/0008-5472.can-14-0836
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Adaptive Immunity by IL9 Can Be Disrupted to Achieve Rapid T-cell Sensitization and Rejection of Progressive Tumor Challenges

Abstract: The tolerogenic cytokine IL-9 promotes T regulatory cell function and allergic airway inflammation, but it has not been extensively studied in cancer. In this report, we employed IL-9 deficient mice to investigate the effects of IL-9 in multiple models of breast and colon cancer development. Eliminating endogenous IL-9 enabled sensitization of host T cells to tumors, leading to their early rejection without the requirement of vaccines or immunomodulatory therapies. Notably, IL-9-deficient mice acquired immunol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 37 publications
3
46
0
1
Order By: Relevance
“…The role of T H 9‐derived IL‐9 remains controversial in the context of tumor immunology. Hoelzinger and colleagues suggested that neutralization of IL‐9 helped alleviate tumor burdens while other studies suggested a beneficial (protective) role for IL‐9 against B16 melanoma cells through a multivariate effector response . Importantly, Purwar et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of T H 9‐derived IL‐9 remains controversial in the context of tumor immunology. Hoelzinger and colleagues suggested that neutralization of IL‐9 helped alleviate tumor burdens while other studies suggested a beneficial (protective) role for IL‐9 against B16 melanoma cells through a multivariate effector response . Importantly, Purwar et al .…”
Section: Discussionmentioning
confidence: 99%
“…A recent report suggested that the development of T H 9 immunity arises from a failure to mount a T H 17 response . In vitro , the addition of a combination of TGF‐β and IL‐4 can yield IL‐9 producing CD4+ cells by down regulating the DNA‐binding inhibitor Id3, thereby allowing for an enhancement in the binding of the transcription factors E2A and GATA‐3 to the il9 promoter region . A recent study suggested that the stimulation of glucocorticoid‐induced tumor necrosis factor receptor (TNFR)‐related protein (GITR) signaling favors the development of T H 9 cells in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that high TGF-β levels in responders prior to treatment may allow increased induction of Th9 cells upon anti-PD-1 treatment, which in turn may improve cytotoxic anti-tumor immune responses [52] . However, it should be noted that the role of Th9 cells in antitumor immunity is still controversial with various studies suggesting that IL-9 can either promote or inhibit anti-tumor immune responses [53][54][55] .…”
Section: Predicting the Efficacy Of Anti-pd-1/ Ctla-4 Treatmentsmentioning
confidence: 99%
“…Un ralentissement de la croissance tumorale a été observé chez des souris porteuses de tumeurs coliques après vaccination par un lysat de cellules isolées de tumeurs coliques associé à de l'alun. Le développe-ment d'une réponse de type Th2, au sein de la tumeur, [41]. Le rejet des tumeurs chez ces souris est conditionné par la présence de lymphocytes T CD4 et surtout T CD8 dont la déplétion rétablit la progression tumorale.…”
Section: Maladies Auto-immunesunclassified